2018
DOI: 10.1158/1535-7163.mct-17-0193
|View full text |Cite
|
Sign up to set email alerts
|

A Tricin Derivative from Deschampsia antarctica Desv. Inhibits Colorectal Carcinoma Growth and Liver Metastasis through the Induction of a Specific Immune Response

Abstract: In colorectal carcinoma patients, distant metastatic disease is present at initial diagnosis in nearly 25% of them. The majority of patients with metastatic colorectal carcinoma have incurable disease; therefore, new therapies are needed. Agents derived from medicinal plants have already demonstrated therapeutic activities in human cancer cells. Antartina is an antitumor agent isolated from Desv. This study aimed to evaluate the antitumor properties of Antartina in colorectal carcinoma models. We used human an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Deschampsia antarctica is expected to be rich in molecules with anticancer activity (Silva et al, 2020). For example, a tricin derivative form D. antarctica inhibits the growth of colorectal cancer and liver metastasis (Malvicini et al, 2018). is usefulness is another important reason for studying these plants in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Deschampsia antarctica is expected to be rich in molecules with anticancer activity (Silva et al, 2020). For example, a tricin derivative form D. antarctica inhibits the growth of colorectal cancer and liver metastasis (Malvicini et al, 2018). is usefulness is another important reason for studying these plants in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies on D. antarctica have included the search of genes expressed under cold stress [17], the later development of cold resistant transgenic rice plants [18] and the resistance to oxidative stress after exposure to UVB radiation [19]. Recently, the effect of Antartina TM , which was developed from extracts of D. antarctica , has been evaluated as an inhibitor of colorectal carcinoma growth and liver metastasis [20].…”
Section: Introductionmentioning
confidence: 99%
“…Tricin (4′,5,7-trihydroxy-3′,5′-dimethoxyflavone) identified from various plants is reported to inhibit the growth of colorectal carcinoma [ 1 ] and breast cancer cells [ 2 ] as well as influenza virus activity [ 3 ]. Several studies have demonstrated that tricin isolated from Njavara rice has anti-inflammatory and antioxidative properties [ 4 , 5 ]; tricin and its derivatives isolated from Zizania latifolia (ETZL) were previously identified as the active components for inhibition of allergies and inflammation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%